Notes on Communication Nevesinje–Anderba and settlements near the road - Samardžić, Gligor M. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
In this paper we have presented the data regarding the Roman communication Nevesinje-Anderba (East Herzegovina) and the settlements near the road. From Nevesinje the road led eastern towards Gacko and there it was bifurcated. One siding led towards east for Anderba, and the other towards north, deeper in Dalmatia, towards Podrinje. Archeological founds from Gacko and Nevesinje proved that this area relatively early was connected with the network of Roman communications. Roman settlements in the area of Nevesinje and Gacko were found on numerous locations. Population density of this area (remnants of Roman settlements) and archeological founds (remnants of the road and mileposts) proved the existence of communication which spread from Nevesinje towards Gacko, and further over the verge of Gatacko Polje, Avtovac, Kazanci and from this point the communication entered the territory of Montenegro. From the town of Niksic in Montenegro the road was connected with the communication Narona–Scodra.